INTERDISCIPLINARY APPROACH IN THE THERAPY OF IMPACTED SECOND AND THIRD MOLARS - Gerasimova, Sofija; Markovska, Mirjana; Maneva, Marija; Radeva, Maja; Simjanovska, Ljuba; Chadikovska, Elizabeta (Journal of Morphological Sciences, 2019)
Simultaneous impactions of second and third permanent molars are a very rare clinical situation with different therapeutic approaches. Impaction of mandibular second molar sometimes can be challenging and frustrating for orthodontics and oral surgeons. Treatment depends on degree of tooth inclination and position of the third molars. Early diagnosis and good treatment for mandibular molar impaction is recommended between age 11 and 14, 27, 28, 29 when root formation is not yet complete. Conservative treatments of second mandibular molar impaction are successful in about 50% of cases. The treatment of impacted second molars (maxillary and mandibular) may be extraction of the second molar to permit the third molar to replace it, surgical exposure, orthodontic traction, surgical luxation and orthodontic traction, restoration, transplantation or no treatment. This paper reports unusual cases of unilateral mandibular and maxillary second and third molar impaction diagnosed radiographically followed  by orthodontic treatment. Key words:impaction, molars, orthodontic treatment